ANALISIS PENGARUH INFLASI DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KERINCI - Dewi Ernita (Gapenas Publisher, 2021)
Regional development as an integral part of national development. The dependence of regional government funds on the central government also reflects the government's limited ability to accumulate Regional Original Revenues (PAD). To improve the implementation of development funds for the provision of community services and to increase economic growth in the regions, it is necessary to provide adequate local sources and income. Inflation is one of the important economic indicators that can provide information about the development of prices of goods and services paid by consumers. Kerinci Regency's Regional Original Revenue (PAD) has increased every year along with the increase in GRDP accompanied by fluctuations in inflation due to economic growth that occurred in Kerinci Regency. This study is to determine the effect of inflation and GRDP on Original Income in Kerinci Regency. The data used are secondary data where the regression analysis method becomes the analysis tool used. The results of the study, GDP and inflation affect Kerinci regency's Original Regional Revenue